2016
DOI: 10.1002/pmic.201600229
|View full text |Cite
|
Sign up to set email alerts
|

The proteome of normal human retrobulbar optic nerve and sclera

Abstract: The optic nerve is a white matter tract that conveys visual information to the brain. The sclera comprises the white, protective outer layer of the eye. A characterization of the proteome of normal human retrobulbar optic nerve and sclera may facilitate studies of the eye. We conducted a proteomic analysis of optic nerve and sclera from five adults. Proteins were fractionated using SDS-PAGE. After in-gel digestion, peptides were analyzed using LC-MS/MS on an Orbitrap Elite mass spectrometer. We identified 2711… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…They were subjected to blast analysis to find conserved retinal-specific proteins. [8][9][10]14 Further, ID match analysis was performed between dataset 1 (609 proteins) and dataset 2 (672 proteins) to identify dataset 3 (338 proteins) consisting of conserved corneal specific proteins. Further, the corresponding sequences were batch retrieved from Uniprot database.…”
Section: Peptide Designing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…They were subjected to blast analysis to find conserved retinal-specific proteins. [8][9][10]14 Further, ID match analysis was performed between dataset 1 (609 proteins) and dataset 2 (672 proteins) to identify dataset 3 (338 proteins) consisting of conserved corneal specific proteins. Further, the corresponding sequences were batch retrieved from Uniprot database.…”
Section: Peptide Designing Strategymentioning
confidence: 99%
“…Semba et al 7 published a series of articles on human eye proteome [8][9][10] listing out the set of abundant proteins in different parts of the eye (choroid, retina, lens, iris, ciliary body, etc). Dyrlund et al 11 identified and quantified the list of proteins in the layer of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this observation needs to be substantiated by further experiments. Further, we analyzed the schisis fluid-specific proteins with the proteome data sets of various ocular tissues such as the retina, ciliary body, iris, retinal pigment epithelium, choroid, sclera and optic nerve [2325]. On comparison, we found that 257 (33%) schisis fluid proteins were not detected in any of the ocular tissues including the vitreous fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports also used mass spectrometry‐based proteomics to profile the ocular surface. In particular, the Human Eye Proteome Project aims to characterize all sub‐proteomes of the healthy eye and profile the tear proteome . Additional studies have also profiled ocular protein level differences following chemical exposure and during macular degeneration .…”
Section: Introductionmentioning
confidence: 99%